1986
DOI: 10.1021/om00132a009
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses, x-ray structures, and cis-trans isomerism of (pentamethylcyclopentadienyl)dicarbonylrhenium dihalides (.eta.-C5Me5)Re(CO)2X2 (X = Cl, Br, I)

Abstract: Cis and trans isomers have been synthesized for the series of rhenium dicarbonyl dihalides Cp*Re(CO)2X2(Cp* = i)-C5Me5•, X = Cl, Br, I). The cis isomers were formed by reaction of Cp*Re(CO)2(N2) with HX and were converted to the trans isomers by UV irradiation in hexane. The structures of the isomers have been assigned from examination of r(CO) IR intensities and are supported by X-ray structure determinations on cts-Cp*Re(CO)3I2 and frans-Cp*Re(CO)2Br,. Crystal data for c¿s-Cp*Re(CO)2I2: monoclinic P21/n, a =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
36
0
1

Year Published

1986
1986
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 0 publications
13
36
0
1
Order By: Relevance
“…For this series of rhenium complexes we found that cis-trans isomerism was a result of dissociative loss of CO to generate a single intermediate, regardless of the starting isomer used, which reacted with free CO to produce a trans geometry in the product, reaction [I]. This was in agreement with reports of the room temperature solution studies which indicated the observation of only cis-trans isomerism for these Re complexes (2).…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…For this series of rhenium complexes we found that cis-trans isomerism was a result of dissociative loss of CO to generate a single intermediate, regardless of the starting isomer used, which reacted with free CO to produce a trans geometry in the product, reaction [I]. This was in agreement with reports of the room temperature solution studies which indicated the observation of only cis-trans isomerism for these Re complexes (2).…”
Section: Introductionsupporting
confidence: 90%
“…The reaction, given by reaction [2], is a geometrical isomerism of the basal ligands. Unlike the rhenium complexes, the molybdenum complexes were reported to undergo isomerism in either direction via photochemical initiation.…”
Section: Introductionmentioning
confidence: 99%
“…: 78 °C (Zers.)) [7] [8], während wir für die purpurfarbenen Kristalle auf der Basis IR-spektroskopischer Befunde (feh lende r(C O )-, charakteristische v(CH)-, v(CC)-und v(R e-C l)-A bsorptionen) und in Analogie zum homologen Cp2ReCl die Struktur Cp*2ReCl vorschlagen [9], Die Acyl-Komplexe 2 a und 2 b lassen sich direkt in Verbindungen mit einer Metall-KohlenstoffDreifachbindung überführen. So führt die Um set zung von 2 b mit Oxalylbromid in C H 2C12 bei -6 0 °C direkt zum Carbin-Komplex [Cp*(CO)2-R e=C P h]B r (5b), welcher nach chrom atographi scher Reinigung an silanisiertem Kieselgel bei -3 0 °C mit 80% Ausbeute als leuchtend-gelber, in C H 2C12 sehr gut, in Pentan dagegen unlöslicher Feststoff isoliert wird (Gl.…”
Section: O Phunclassified
“…: 9 7 -9 8 °C. EI-MS (70 eV), m /z (% ): 424,3 (17,9) [Cp*(CO)2TcC (O Et)Ph]+, 396,3 (27,3) [C p*(C O )TcC (O Et)Ph]+, 368,4 (5,4) [Cp*TcC(O Et)Ph]+, 339,2 (24,8) …”
Section: Icarbonyl[(ethoxy) (Phenyl)carben] ( Rj5-penta M Ethylcyclmentioning
confidence: 99%
See 1 more Smart Citation